A link between ghrelin and major depressive disorder: a mini review - Lis, Michał; Miłuch, Tymoteusz; Majdowski, Maciej; Zawodny, Tomasz (Frontiers in Psychiatry, 2024)
Ghrelin is primarily responsible for regulating energy balance, as it increases appetite. However, in recent years, its new physiological functions have been discovered—it regulates lipogenesis, plays a role in the development of insulin resistance, and even acts protectively on heart muscle. Moreover, ghrelin was associated with many psychiatric disorders, including major depressive disorder (MDD) or schizophrenia. Ghrelin levels were elevated in patients diagnosed with depression and in patients after suicide attempts. Moreover, ghrelin was connected to depression among postmenopausal women and was shown to be a predictive marker of MDD among the elderly. Ghrelin may influence mood disorders in various ways: by regulating stress response or inflammation or altering neurotransmission in the amygdala, dorsal raphe nucleus, or hippocampus, brain regions previously connected to the pathophysiology of MDD. Genetic variants of ghrelin and its receptor have also been associated with depression. Moreover, ghrelin can interfere with the antidepressant’s action and may play a role in treatment resistance. This review highlights ghrelin’s role in depression, summarizes the existing knowledge on the subject, and presents ideas for further research.